2019
DOI: 10.1136/rapm-2018-100075
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided subomohyoid suprascapular nerve block and phrenic nerve involvement: a cadaveric dye study

Abstract: Backgrounds and objectivesThe anterior approach to the subomohyoid suprascapular (SOS) nerve is a new, technically easy and reliable regional anesthesia technique for postoperative shoulder analgesia. However, due to its proximity, the injectate may spread to the brachial plexus and phrenic nerve. The goal of this anatomic study with dye injection in the subomohyoid space and subsequent cadaver dissection was to establish the likely spread of local anesthesia and the extent of brachial plexus and phrenic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Our findings present consistent evidence of superior trunk blockade when a suprascapular block is performed, indicating that blockade of the superior trunk is a major underlying mechanism to the observed efficacy of suprascapular block. These results provide the clinical correlation of the earlier anatomic studies of Sehmbi et al 17 (who reported 90% staining of the brachial plexus), Laumonerie et al 14 (who reported 100% staining of the superior trunk), and Siegenthaler et al 13 (who reported brachial plexus block even when a 0.1 ml volume of injectate is used). The Downloaded from anesthesiology.pubs.asahq.org by guest on 07/16/2020 consistent spread to the superior trunk observed also offers a plausible explanation for the historical discrepancy in analgesic effects relative to interscalene block observed between the posterior suprascapular block (inferior to interscalene block) [8][9][10] and the suprascapular block (noninferior to interscalene block).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings present consistent evidence of superior trunk blockade when a suprascapular block is performed, indicating that blockade of the superior trunk is a major underlying mechanism to the observed efficacy of suprascapular block. These results provide the clinical correlation of the earlier anatomic studies of Sehmbi et al 17 (who reported 90% staining of the brachial plexus), Laumonerie et al 14 (who reported 100% staining of the superior trunk), and Siegenthaler et al 13 (who reported brachial plexus block even when a 0.1 ml volume of injectate is used). The Downloaded from anesthesiology.pubs.asahq.org by guest on 07/16/2020 consistent spread to the superior trunk observed also offers a plausible explanation for the historical discrepancy in analgesic effects relative to interscalene block observed between the posterior suprascapular block (inferior to interscalene block) [8][9][10] and the suprascapular block (noninferior to interscalene block).…”
Section: Discussionsupporting
confidence: 82%
“…Owing to anatomical proximity and proximal spread, 15,16 performing an anterior suprascapular nerve block under the inferior belly of the omohyoid muscle in the supraclavicular fossa seems to consistently block the superior trunk and brachial plexus, even when very small local anesthetic volumes are used. [15][16][17] Consequently, we thought that the subomohyoid anterior suprascapular block is another approach to superior trunk block that blocks the majority of shoulder innervation, thus providing postoperative analgesia that is not worse than the interscalene block for shoulder surgery.…”
mentioning
confidence: 99%
“…In other words, no matter how complete, a targeted suprascapular nerve block still ignores the important roles played by the axillary, lateral pectoral and subscapular nerves in the innervation of the shoulder. A more plausible explanation could be inferred from recent cadaveric studies conducted by Laumonerie et al 44 and Sehmbi et al 45. These authors observed that an anterior suprascapular block with 5–10 mL of a mixture containing methylene blue results in retrograde staining of the upper and middle trunks 44 45.…”
Section: Current Understanding Of Diaphragm-sparing Nerve Blocksmentioning
confidence: 97%
“…A more plausible explanation could be inferred from recent cadaveric studies conducted by Laumonerie et al 44 and Sehmbi et al 45. These authors observed that an anterior suprascapular block with 5–10 mL of a mixture containing methylene blue results in retrograde staining of the upper and middle trunks 44 45. Therefore, the term ‘anterior suprascapular nerve block’ may be somewhat of a misnomer, as LA spread is not solely confined to the suprascapular nerve.…”
Section: Current Understanding Of Diaphragm-sparing Nerve Blocksmentioning
confidence: 99%
See 1 more Smart Citation